The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/jfb.12074
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale movements and habitat use of juvenile southern flounder Paralichthys lethostigma in an estuarine seascape

Abstract: Habitat use of juvenile southern flounder Paralichthys lethostigma was examined within a shallow estuarine seascape during June and July 2011 using acoustic telemetry. Fine-scale movement and habitat use of P. lethostigma was investigated with an acoustic positioning system placed in a seascape that varied in habitat type, physicochemical conditions and bathymetry. The use of different habitat types was examined with Euclidean distance-based analyses, and generalized additive models were used to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…Our results confirm the usefulness of this technique in improving the quality of the positioning [7]. In many studies, the HPE threshold is set between 10 and 20 [16,17,23,24] but this choice is seldom discussed or objectively assessed. In the environmental conditions experienced in this study, we observed a large variability in the number of calculated positions and the mean positioning error for HPE filters between 10 and 20.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results confirm the usefulness of this technique in improving the quality of the positioning [7]. In many studies, the HPE threshold is set between 10 and 20 [16,17,23,24] but this choice is seldom discussed or objectively assessed. In the environmental conditions experienced in this study, we observed a large variability in the number of calculated positions and the mean positioning error for HPE filters between 10 and 20.…”
Section: Discussionsupporting
confidence: 81%
“…The VPS can estimate fine-scale positional information on multiple tagged animals simultaneously over a large area [9]. This system is now widely used in fish behavior studies in marine and freshwater environments [7,[14][15][16][17][18][19][20]. However, its performance has not yet been extensively documented (but see [7]).…”
Section: Introductionmentioning
confidence: 99%
“…With the VPS system, little effort has been made to defend filtering cutoffs beyond reference to prior use [13], and ambiguous filter criteria are at risk of inadvertently becoming acceptable practice through the accumulation of use. In our case, adoption of an ambiguous filter based on a previous study (HPE 10 to 20 [14][15][16]), would have been less useful than the carefully evaluated filter cutoff of 8 and indefensible (Table 2). Telemetry technology represents a very different tool than typical scientific instruments as its design is rarely consistent, is difficult to standardize, and does not generate data points with fixed accuracy and precision.…”
Section: Discussionmentioning
confidence: 68%
“…Studies either used a conservatively high HPE cutoff to remove the major problematic positions but retain most data (e.g., for an HPE number of 20, 83% retention [14]), or employed a lower HPE cutoff for the study and sacrificed large amounts of data (e.g., for an HPE number of 10, 58% retention [15]). In other cases, HPE was used but the level of data reduction was not reported (for an HPE number of 15 [12]), no filtering occurred and the HPE estimated for synchtags was assumed to characterize the precision of all animal positions in the array [10], or the authors referenced an example of the accuracy attained from a similarly configured array used in an unrelated study [16].…”
Section: Filtering Spatial Data With Hpementioning
confidence: 99%
“…We assumed that fish of this size would be able to handle the tag burden, as researchers in other studies have tagged Winter Flounder Pseudopleuronectes americanus smaller than 19 cm (Fairchild et al 2009) and other Paralichthys spp. at similar sizes compared to the halibut in our study (Furey et al 2013). Surgical implantation of tags in other species of flatfish appears to have had no effects on feeding and activity behavior (Moser et al 2005).…”
Section: Fish Movements As An Estuary Restoration Metricmentioning
confidence: 56%